Easma Fibrinopeptide A And β-Thrombogloblin In The Patients With Thrombotic Disorders - Murakoshi, T; Takei, H; Seya, T; Oguma, Y; Yamauchi, M; Hasegawa, H (Thrombosis and Haemostasis, 1981)
Fibrinopeptide A(FPA) is a sensitive indicator of the thrombin action and β-thrombogloblin(β-TG) is a useful marker of the platelet activation. In order to know the coagulation disturbances in thrombotic disorders, the measurement of the two indicaters is very important. However, relationship between these two indicators is not well studied. We measured plasma FPA and β-TG levels in the patients with decompensated DIC, lung cancer, gastric cancer, leukemia, thrombosis, and ARDS. In addition, influences of heparin and urokinase on-plasma FPA and β-TG levels were investigated. Plasma FPA and β-TG levels were eleveted in decompensated DIC(mean FPA: 14.0 ng/ml, mean β-TG:73.9 ng/ml), but in some cases, these two indicators didn’t change in the same manner. This difference was thought to be due to the concentration of plasma fibrinogen and a number of platelets. In the patients with lung cancer, elevated FPA and β-TG levels were found, and the former was elevated with progress of clinical stage. In some patients with leukemia, reduced β-TG levels due to hypoproduction of platelet were found in contrast to elevated FPA levels. On the other hand, in the patients with gastric cancer complicated with DIC, FPA levels elevated very slightly possibly due to extremely low concentration of fibrinogen, and β-TG levels showed a significant elevation. These results suggest that the measurement of both FPA and β-TG lead us to precise and accurate comprehension of coagulation abnormality. In the patients with overcompensated DIC, elevated FPA and β-TG levels(mean FPA:11.7, mean β-TG:98.0 ng/ml) were found, indicating hypercoagulability. Additionaly, we tried to use the ultrafiltration apparatus instead of dialysis tubing to shorten a time required for FPA assay, because dialysis tubing for plasma dialysis requires a lot of time, and is inappropriate for clinical investigation, especially in an emergency.